2007
DOI: 10.1016/j.ijfoodmicro.2007.04.014
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of fumonisins B1 and B2 in broa, typical Portuguese maize bread

Abstract: Fumonisin B 1 (FB 1 ) and fumonisin B 2 (FB 2 ) are mycotoxins mainly produced by Fusarium verticillioides, and Fusarium proliferatum, fungi species most commonly isolated from maize. The natural occurrence of FB 1 and FB 2 in broa, typical Portuguese maize bread, was evaluated in 30 samples. Twenty five were found positive with levels ranging from 142 to 550 μg kg − 1 . The limit established by the European regulations was exceeded by 27% of the samples. The tolerable daily intake for fumonisin B 1 , and B 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
1
2

Year Published

2008
2008
2013
2013

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(22 citation statements)
references
References 22 publications
0
19
1
2
Order By: Relevance
“…These results were lower than those obtained in other studies for maize, wheat, rice and barley products (Castella, Bragulat, & Cabanes, 1999;Cavaliere et al, 2007;Weidenboerner, 2000). FBs were not detected in maize samples, while other studies found a high incidence and concentration levels of FBs in maize and maize products (Lino, Silva, Pena, Fernández, & Mañes, 2007;Martins, Almeida, Marques, & Guerra, 2008;Silva, Lino, Pena, & Moltó, 2007;Silva, Lino, Pena, & Moltó, 2009). Martos, Thompson, and Diaz (2010) and Klaric et al (2009) did not detect FBs in wheat grain samples, but in the present study FB2 was detected.…”
Section: Fumonisinscontrasting
confidence: 58%
“…These results were lower than those obtained in other studies for maize, wheat, rice and barley products (Castella, Bragulat, & Cabanes, 1999;Cavaliere et al, 2007;Weidenboerner, 2000). FBs were not detected in maize samples, while other studies found a high incidence and concentration levels of FBs in maize and maize products (Lino, Silva, Pena, Fernández, & Mañes, 2007;Martins, Almeida, Marques, & Guerra, 2008;Silva, Lino, Pena, & Moltó, 2007;Silva, Lino, Pena, & Moltó, 2009). Martos, Thompson, and Diaz (2010) and Klaric et al (2009) did not detect FBs in wheat grain samples, but in the present study FB2 was detected.…”
Section: Fumonisinscontrasting
confidence: 58%
“…Recently, several new sources of fumonisins have been reported, e.g. cornflakes (Castells, Marin, Sanchis, & Ramos, 2008), the Portuguese maize bread broa (Lino, Silva, Pena, Fernandez, & Mañes, 2007), black and herbal tea as well as medicinal plants (Martins, Martins, & Bernardo, 2001;…”
Section: Analytical Methods For Identification Of Fumonisinsmentioning
confidence: 99%
“…Maize flour for breadmaking was traditionally obtained in stone wheel mills, moved by water or wind, and nowadays frequently by electricity. There are many recipes to prepare broa, but the traditional process (Lino et al 2007) involves adding maize flour (sieved whole meal flour), hot water, wheat flour, yeast and leavened dough from the late broa (acting as sourdough). After mixing, resting and proofing, the dough is baked in a wood-fired oven.…”
Section: Introductionmentioning
confidence: 99%